Aflatoxin B1 effects on the ovarian follicles of White Leghorn laying hens - HASANZADEH, S; SHAHROOZ, R; SADRKHANLOU, R (The Indian Journal of Animal Sciences, 2014)
The objective of this study was to investigate low dose and long duration effects of aflatoxin B1 on different categories of the ovarian follicles in adult White Leghorn layers. The birds were put in 2 groups, viz. experiment and as controls. Every chicken of experiment group was received AFB1 @ 0.62 ppm/day through oral route for the duration of 120 days. At the end of experiment, all the birds were slaughtered, immediately their ovaries collected and preserved in 10% buffered formaldehyde solution. In both the groups, the macroscopic follicles i.e. SWF, SYF, LYF (including F1, F2, F3, F4, F5), and POF were recorded, and then the specimens were subjected to tissue preparation, for histomorphologic and histomorphometric studies. All types of ovarian follicular distributions (including healthy and atretic) were recorded. There was highly significant (P